English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

can you explain how to get to the answer please.

2006-09-18 15:06:30 · 4 answers · asked by mylipshot 2 in Science & Mathematics Mathematics

4 answers

-3 - 4(t - 5) = -2(t + 3) + 11
-4(t - 5) = -2(t + 3) + 14
-4(t - 5) = -2((t + 3) - 7)
2(t - 5) = (t + 3) - 7
2t - 10 = t + 3 - 7
2t - 10 = t - 4
t = 6

2006-09-18 17:54:52 · answer #1 · answered by Sherman81 6 · 0 0

-3-4(t-5)=-2(t+3)+11 multipy parenthesis to get:
-3-4t+20=-2t-6+11 add 4t to both sides and simplify numbers:
17=2t+5 subtract 5 from both sides:
12=2t divide both sides by 2:
6=t

then plug it into the equation to verify

Just remember that you can do anything you want to an equation, as long as you do the same thing to both sides.

2006-09-18 22:14:53 · answer #2 · answered by kelsey 7 · 1 0

T=6!!!!!

2006-09-18 23:13:09 · answer #3 · answered by The Apostle 2 · 0 0

-3-4(t-5)=-2(t+3)+11 (Firstly expand your equation and you get the following)
-3-4t+20 = 2t + 6 + 11 (Now simplify your equation and you get the following)
17 - 4t = 2t + 17 (Now shift the t to one side and you get the following)
-4t - 2t = 17 - 17 (Now simplify your equation and you get the following)
-6t = 0
t =0


Thats your answer.

Cheers

2006-09-18 22:30:56 · answer #4 · answered by isz_rossi 3 · 0 1

fedest.com, questions and answers